Urinary exosomal miRNA-663a shows variable expression in diabetic kidney disease patients with or without proteinuria - Sinha, Nisha; Puri, Veena; Kumar, Vivek; Nada, Ritambhra; Rastogi, Ashu; Jha, Vivekanand; Puri, Sanjeev (Scientific reports, 2023)
Heterogeneity in the Diabetic Kidney Disease (DKD) diagnosis makes its rational therapeutics challenging. Although albuminuria characterizes DKD, reports also indicate its prevalence among non-proteinuric. Recent understanding of disease progression has thus inclined the focus on proximal tubular cell damage besides the glomeruli. A non-invasive approach exploiting exosomal miRNA derived from human kidney proximal tubular cell line was, hence, targeted. Upon miRNA profiling, three miRNAs, namely, hsa-miR-155-5p, hsa-miR-28-3p, and hsa-miR-425-5p were found to be significantly upregulated, while hsa-miR-663a was downregulated under diabetic conditions. Among these, hsa-miR-663a downregulation was more pronounced in non-proteinuric than proteinuric DKD subjects and was thus selected for the bioinformatics study. Ingenuity Pathway Analysis (IPA) narrowed on to IL-8 signaling and inflammatory response as the most enriched ‘canonical pathway’ and ‘disease pathway’ respectively, during DKD. Further, the putative gene network generated from these enriched pathways revealed experimentally induced diabetes, renal tubular injury, and decreased levels of albumin as part of mapping under ‘disease and function’. Genes target predictions and annotations by IPA reiterated miR-663a’s role in the pathogenesis of DKD following tubular injury. Overall, the observations might offer an indirect reflection of the underlying mechanism between patients who develop proteinuria and non-proteinuria.